Lydene er musikkens græsrødder. Nogle betragtninger over lyd og rum - Westman, Bror (Tidsskriftet Antropologi, 2019)
Sound is characterised by distinctive phenomenological qualities. It creates a ‘sound scape’ that - as space sensed through the ears - wraps itself around the listener as an intimate atmosphere, without distance and clear dimensionality. Sounds are deeply interwoven with religious symbolism, e.g. as shamans incantate or pick up the auditory signals of gods or spirits. Cultural sound control spaces. Nostalgically, the church bells filled the parish, as today the ‘holy noise’ of traffic filis the urban spaces. But noise can also be used as artistic material, as in the works of the composer Russolo or in the planned landscape opera created by Winther, Hagen and the author.